Social Actions of Rex Walls’ The Glass Castle: A Weberian Analysis - Nikmah, Devita Lailatun (Journal of Literature, Linguistics, & Cultural Studies, 2024)
This research aims to describe the kinds of social actions carried out by one of the main characters named Rex Sevanson Walls in Jeannette Walls’ book entitled The Glass Castle, and to find out how the contribution of social actions in Rex Walls' life is to achieve his goals. The researcher uses Social Action Theory by Max Weber, and uses a sociology of literature approach. Researchers collect data by reading the novel periodically, highlighting, and collecting the data relevant to the formulation of the problems and theories taken. After collecting the data, the researcher analyzed and entered the data into the social action component proposed by Max Weber. Rex Walls’ social action found by researcher includes all components of Max Weber’s social action. Rex Walls’ dominant form of social actions is affectual action. With the following details; there are four instrumentally rational actions, then there are two value rational actions, there are five affectual actions and there are four actions in the form of traditional actions. Then, the researcher concludes how social action contributes in Rex Walls’ life to achieve his goals. The purpose of the social action carried out by Rex Walls, namely; develop the character of their children, and be a good father figure for them. The contribution of social action to Rex Walls’ life is to make Rex Walls feel fulfilling his obligations as a father.